Integration of Electrospray and Digital Light Processing for Freeform Patterning of Porous Microstructures. Issue 11 (16th October 2020) - Xue, Yue; Qi, Lin; Niu, Ye; Huang, Hanyang; Huang, Fangsheng; Si, Ting; Zhao, Yi; Xu, Ronald X.
Abstract: An electrospray photolithographic patterning (EPP) process that integrates advantages of electrospray (ES) and digital light processing (DLP) for maskless fabrication of 3D porous microstructures is proposed here. First, monodisperse microparticles with controllable particle size produced by ES are deposited on a substrate to form a photoresist layer. Second, DLP exposure of the photoresist layer selectively irradiates the microparticles to form a desired pattern with complexity. Third, the repetitive steps of deposition and exposure enable layer‐by‐layer construction of a green part with embedded 3D patterns of irradiation. Finally, the irradiated microparticles are removed from the green part to form 3D particulate microstructures. With this process, freeform patterning of multiple micro‐electro‐mechanical system elements with controlled porosity, involving microfluidic channels, stamps, and power‐free pressure sensors is successfully demonstrated. The EPP process has a great technical potential for freeform and high‐throughput fabrication of multi‐layered porous microstructures in versatile applications such as micromixers, porous stamping, and microsensors. Abstract : An electrospray photolithographic patterning (EPP) process is proposed by integrating advantages of electrospray and digital light processing. The assembly‐free and freeform fabrication of multi‐layered porous microstructures including microfluidic channels, stamps, and power‐free pressure sensors is successfully demonstrated. The EPP process has a great technical potential for versatile applications such as micromixers, porous stamping, and microsensors.